Students' Creative Thinking Process in Mathematic Problems Solving Assisted by GeoGebra - Margaretha, Ningrat Delvia; Hidayat, Dayat (Journal of Mathematical Pedagogy (JoMP), 2023)
The purpose of this research is to find out how students' creative thinking process in solving Geogebra-assisted math problems and to find out the obstacles experienced by students in the creative thinking process. This research is a qualitative descriptive research. The subject selection was taken 3 students using purposive sampling method, namely by considering students who were considered able to work on the math problems given and had been able to use GeoGebra. The data collection techniques used in this research were tests and interviews. The main instrument in this research is the researcher himself. Auxiliary instruments are math problems and interview guidelines. The math problem used is a spatial problem to find the volume and surface area with assisted by Geogebra to measure students' creative thinking. Interviews are used to find out how students' creative thinking processes while working on math problems. The analysis used is data reduction, data presentation and conclusion drawing. The results of this reasearch show the student’s creative thinking process in solving math problems assisted by Geogebra. In this reasearch also shows that students experience obstacles at the stage of synthesizing ideas, namely the stage of students gathering information or remembering and combining ideas sourced from previous experiences.